2007
DOI: 10.1590/s0004-282x2007000600006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bromazepam on the early stage of visual information processing (P100)

Abstract: -The early stages of visual information processing, involving the detection and perception of simple visual stimuli, have been demonstrated to be sensitive to psychotropic agents. The present study investigated the effects of an acute dose of bromazepam (3 mg), compared with placebo, on the P100 component of the visual evoked potential and reaction time. The sample, consisting of 14 healthy subjects (6 male and 8 female), was submitted to a visual discrimination task, which employed the "oddball" paradigm. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Last, antipsychotic agents have known effects on neural activation (68, 69). An increase in P100 latency during visual discrimination has previously been shown following an acute dose of bromazepam (70). …”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Last, antipsychotic agents have known effects on neural activation (68, 69). An increase in P100 latency during visual discrimination has previously been shown following an acute dose of bromazepam (70). …”
Section: Introductionmentioning
confidence: 66%
“…Component P100 was measured as the maximal positive deflection between 80 and 120 ms (25) at electrodes O1, OZ, and O2 [established optimal occipital scalp sites; (25, 51, 53, 67, 70)]. Peak latencies and amplitudes from baseline were submitted to repeated measures ANOVA, with task (Mooney and photographic faces) and orientation (upright and inverted) as within-subjects factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and some studies have shown that it triggers changes in neuropsychological functions such as memory, attention, psychomotor activity, reaction time and alertness 7 . Modafinil has already been used for the treatment of narcolepsy and other sleep disorders 8,9,10 .…”
mentioning
confidence: 99%
“…We suggest that other potentials involved in the decision making process, as well as the P100, should be investigated under drug influence, since the first phases of information processing are probably more sensitive to pharmacological effects [36][37][38]. …”
Section: Resultsmentioning
confidence: 99%